Tingkat Kecemasan Pada Ibu Premenopouse Dalam Menghadapi Menopouse di RW 09 Kelurahan Sadang Serang Kecamatan Coblong - Metha Solihati Rayuna (STIKes Karsa Husada Garut, 2015)
One of premenopausal syndrome symptoms: depression (anxiety) caused by penunman hormone estrogen. The fall in estrogen cause a decrease in neurotransmitters in the brain, a neurotransmitter in the brain affecting mood so that if these neurotransmitters low levels, it would appear anxious feelings that trigger depression or stress. 37.9% Based on the study premenopausal women who have suffered from depression penunman estrogen levels. Low estrogen levels have an increased risk to become depressed 3.7 times greater than those who did not experience a decrease in estrogen. Im study aims to determine the level of maternal anxiety in the face of menopause prameopouse in RW 09 Village Sadang Serang District of Coblong. This research type is descriptive research. The population in this study is the mother of 09 premenopausal RW village in Serang District of Coblong Sadang as many as 47 people. The sampling technique in this research is total sampling. Research ie no anxiety (4.2%), mild anxiety (12.76%), anxiety was (49%), severe anxiety (34.04%), severe anxiety did not exist. Premenopausal mother in RW 09 Village Sadang Serang District of Coblong experiencing moderate levels of anxiety in the face of menopause as many as (49%). Suggestion : for premenopausal mothers should increase knowledge about menopause by reading leaflets, counseling by health workers, and more active in neighborhood health center to ask the elderly because it is very beneficial for oneself in the face of menopause.